Spectrophotometric Determination of Iridium(III) with Phenanthrenequinonemonosemicarbazone - Rai, H.C.; Chakraborti, I. (Asian Journal of Chemistry, 2010)
When phenanthrenequinonemonosemicarbazone (PQSC) reacts with iridium(III) a brown precipitate is formed on heating. The precipitate is partially soluble in ethanol and chloroform and soluble in dimethytformamide. Because of the intensity and stability of the colour formed with iridiurn(III) this system has been studied in detail with a view to utilise this reaction for the spectrophotometric determination of the metal.